Ribes diacanthum Pall (RDP) ameliorates UUO-induced renal fibrosis via both canonical and non-canonical TGF-β signaling pathways in mice. (1st March 2019) - Gu, Lifei; Wang, Yange; Yang, Guolin; Tilyek, Akhtolkhyn; Zhang, Chunlei; Li, Shaoheng; Yu, Boyang; Chai, Chengzhi; Cao, Zhengyu
Abstract: Ethnopharmacological relevance: Ribes diacanthum Pall (RDP), a folk medicine, has been widely used in Mongolia to treat urinary system diseases. Aim of the study: To investigate the effectiveness of RDP on unilateral ureteral obstruction (UUO)-induced renal interstitial fibrosis and the underlying mechanisms. Materials and methods: A total of 60 mice were randomly divided into six groups: sham group, sham plus RDP (40 mg/kg) group, UUO model group, and UUO model plus RDP (10, 20 or 40 mg/kg) groups. After surgery, aqueous extract of RDP were administrated intragastrically ( i.g ) daily for a week and ipsilateral kidneys were collected seven days after surgery. Levels of blood urea nitrogen (BUN) and serum creatinine (Scr) were detected to reflect the kidney injury. Hematoxylin & eosin and Masson's trichrome staining were used to evaluate the kidney morphological changes and fibrosis, respectively. ELISA was used to examine the levels of pro-inflammatory cytokines. Immunohistochemistry, western blot and PCR were used to examine the expression levels of key proteins involved in transforming growth factor (TGF-β)/Smad and mitogen-activated protein kinase (MAPK) signaling pathways. Results: RDP treatment attenuates the level of BUN and kidney fibrosis in UUO mice, decreases the expressions of interleukin-6, tumor necrosis factor-α, Interleukin-1α, TGF-β1, monocyte chemotactic protein-1, α-smooth muscle actin, collagen I, fibronectin, and vimentin, while increases the expressions of E-cadherin and hepatocyte growth factor. Moreover, RDP administration significantly decreases the levels of p-Smad2/3, p-ERK1/2, p-p38 and p-JNK, while increases the expression level of Smad7 in UUO models. Conclusion: These data demonstrate that RDP ameliorates renal fibrosis through TGF-β/Smad and MAPK pathways in a UUO mouse model. Graphical abstract: